2014
DOI: 10.1111/bjh.13062
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of DNMT3A mutations at long‐term remission in adult patients with AML

Abstract: SummaryMutations in DNMT3A, the gene encoding DNA methyltransferase 3 alpha, have been identified as molecular drivers in acute myeloid leukaemia (AML) with possible implications for minimal residual disease monitoring and prognosis. To further explore the utility of DNMT3A mutations as biomarkers for AML, we developed assays for sensitive detection of recurrent mutations affecting residue R882. Analysis of DNA from 298 diagnostic AML samples revealed DNMT3A mutations in 45 cases (15%), which coincided with mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
4
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 33 publications
7
96
4
4
Order By: Relevance
“…[6][7][8][9][10]32 In these analyses, no prognostic significance of DNMT3A mutation persistence was found. These discrepant results might be explained by the relatively small cohort sizes in some studies, and the focus on a single hotspot codon reflecting only a subset of mutations in one gene, as opposed to a broader panel of driver genes in our study.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…[6][7][8][9][10]32 In these analyses, no prognostic significance of DNMT3A mutation persistence was found. These discrepant results might be explained by the relatively small cohort sizes in some studies, and the focus on a single hotspot codon reflecting only a subset of mutations in one gene, as opposed to a broader panel of driver genes in our study.…”
Section: Discussionmentioning
confidence: 73%
“…[2][3][4][5][6] Several groups have reported frequent persistence of DNMT3A mutations during CR, but found no association with AML relapse or survival. [7][8][9][10] In contrast, in another study analyzing a larger panel of genes in 50 AML patients, mutation persistence associated with shorter event-free and overall survival (OS). 11 Of note, clonal cytogenetic alterations also remain detectable in some patients in morphological remission, and this has been linked to inferior outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…Clonal abnormalities may occur in normal individuals 38 , and recent studies have shown clonal hematopoiesis in normal individuals without evidence of a blood disorder [39][40][41][42] . Interestingly, abnormalities identified as clonal in normal individuals are age-related, with clonal hematopoiesis identified in 0.8% of individuals under 60, rising to 19.5% in those >90 years of age, in a study of 4,219 individuals with investigation of 15 mutation hot spots in blood DNA using ultra-deep sequencing 42 .…”
Section: Mutations In Pathogenesis Of Amlmentioning
confidence: 99%
“…Interestingly, abnormalities identified as clonal in normal individuals are age-related, with clonal hematopoiesis identified in 0.8% of individuals under 60, rising to 19.5% in those >90 years of age, in a study of 4,219 individuals with investigation of 15 mutation hot spots in blood DNA using ultra-deep sequencing 42 . In this study, DNMT3A-R882 mutations, which occur often in CN-AML, were most commonly identified, even in age <25 years, but with normally increased prevalence with age.…”
Section: Mutations In Pathogenesis Of Amlmentioning
confidence: 99%
“…In the case of molecular analyses by RQ-PCR and/or next-generation sequencing, optimal sensitivity thresholds for mutation clearance at CR still need to be established, 26 especially because these sensitive techniques are capable of detecting low levels of fusion transcripts, such as RUNX1-RUNX1T1 or CBFB-MYH11, or mutations in the DNMT3A gene, which are known to persist in patients remaining in durable CR. 26,30 Immunophenotyping using multiparameter flow cytometry can be technically challenging and is relatively expensive, with varying threshold levels proposed for risk stratification. 28 One of the advantages of cytogenetics, despite its limited sensitivity, is that this assay is widely available, also in less developed countries.…”
mentioning
confidence: 99%